Sustained Efficacy, Safety and High Adherence Rate of Onabotulinum Toxin Type A in Chronic Migraine Patients: A Multicentric Prospective Real-Life Study - Ilenia Corbelli; Angela Verzina; Ilaria Leone De Magistris; Gioacchino De Vanna; Paolo Eusebi; Giorgia Mataluni; Antonio Pisani; Addolorata Maria Pia Prudenzano; Maria Trojano; Marianna Delussi; Marina De Tommaso; Antonio Russo; et al. (Toxins, 2022)
Guidelines regarding long-term use with onabotulinumtoxinA (onaBT-A) in chronic migraine (CM) prophylaxis are lacking. This multicentric prospective real-life study aimed to assess the efficacy and safety of a long-term treatment. A total of 195 chronic migraine patients were treated with onaBT-A, every 3 months for 5 cycles (Phase 1). In the Phase 2 of the study, depending on response rate, patients were divided into “responders” (R), “partially responders” (PR) and “non-responders” (NR). Then, we proposed to R and PR patients to continue with an additional 12 months of treatment (additional 4 sessions). Response to treatment and adverse events were collected for the entire duration of the study. Of the 195 patients included (females 82.1%, mean age 47.4 ± 12.4), at the end of Phase 1 there were 52.3% of R patients, 17.9% of PR patients, 15.4% of NR patients and 14.4% drop-outs. During Phase 2 of treatment, R patients presented a maintenance of the improvement achieved during the first year of treatment, as well as PR patients. Except for three serious adverse events not related to treatment, all other adverse events were mild or moderate in severity and resolved without sequelae. In the literature, adherence to oral migraine-preventive medications among patients with CM was found to be less than 25%. The results of this prospective real-life multicenter study show efficacy, safety and adherence to a long-term treatment with onaBT-A.